USAHA PENGEMBANGAN LABU SIAM (Sechium edule (jacq.) sw.) DI KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Sasewa, Demsi R.; Langi, Merry J.J.; Saerang, Apriano (CV Widina Media Utama, 2023)
One of the areas in Indonesia that cultivates chayote plants is in North Sulawesi, precisely in Tomohon City. The temperature in Tomohon City during the day can reach 300C and 18-220C at night. With temperatures like this the author feels it is very suitable for developing pumpkin cultivation, therefore the author is interested in knowing the prospects for developing chayote in Tomohon City. The objectives of this research are (1) to know the production process of chayote (2) to know the prospect of chayote development in East Tomohon District. 1. The conclusion after doing that the production process of chayote research is very easy from planting to harvesting does not really need a lot of labor the maintenance process can be said to be quite easy. With harvest time done every week is very profitable for farmers because they will get weekly income. 2. from the results obtained from the SWOT analysis of the prospects for chayote development in East Tomohon District. It can be concluded that the prospect of chayote development in East Tomohon Subdistrict has an aggressive nature, this is very beneficial for farmers because based on the IFAS value of 2.32 and EFAS of 2.48, it shows that chayote farmers in East Tomohon Subdistrict have the strengths and opportunities to develop the chayote business.ABSTRAKSalah satu wilayah di Indonesia yang membudidayakan tanaman Labu siam adalah di Sulawesi utara tepatnya di Kota Tomohon. Kota Tomohon Suhu di Kota Tomohon pada waktu siang mampu mencapai 300C dan 18-220C pada malam hari. Dengan suhu seperti ini penulis rasa sangat cocok untuk mengembangkan budidaya Labu olehnya penulis tertarik mengetahui prospek pengembangan Labu siam di Kota Tomohon. Tujuan penelitian ini adalah (1) mengetahui proses produksi Labu siam (2) mengetahui prospek pengembangan Labu siam di Kecamatan Tomohon Timur. 1. Kesimpulan setelah melakukan bahwa proses produksi la penelitian labu siam sangat mudah mulai dari penanaman sampai pemanenan tidak terlalu butuhkan banyak tenaga proses perawatan pun bisa di bilang cukup mudah. Dengan waktu panen di lakukan setiap minggu sangat menguntungkan bagi petani karena akan mendapatkan pemasukan mingguan. 2. dari hasil yang didapatkan dari analisis SWOT terhadap prospek pengembangan labu siam di Kecamatan Tomohon Timur. Dapat di simpulkan bahwa prospek pengembangan labu siam di Kecamatan Tomohon Timur memiliki sifat agresif hal ini sangat menguntungkan bagi petani karena berdasarkan nilai IFAS sebesar 2,32 dan EFAS sebesar 2,48 menunjukan bahwa petani labu siam di Kecamatan Tomohon Timur memiliki kekuatan dan peluang untuk mengembangkan usaha labu siam.